2010
DOI: 10.1002/hep.23597
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hypoxia-inducible factor-1α (HIF-1α) versus HIF-2α in the survival of hepatocellular tumor spheroids

Abstract: Hypoxia-inducible factors (HIFs) provoke adaptation to hypoxic stress occurring in rapidly growing tumor tissues. Therefore, overexpression of HIF-1 or HIF-2 is a common feature in hepatocellular carcinoma but their specific function is still controversially discussed. To analyze HIF function in hypoxia-induced cell death we created a stable knockdown of HIF-1a and HIF-2a in HepG2 cells and generated tumor spheroids as an in vitro hepatocellular carcinoma model. Knockdown of HIF-1a enhanced expression of HIF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 29 publications
13
95
1
1
Order By: Relevance
“…Specifically, they showed that small interfering RNA (siRNA) for HIF-1a increases HIF-2a protein, whereas overexpression or siRNA for HIF-2a reduces and increases HIF-1a protein, respectively. This dual effect has been reproduced by others using unrelated cell types (Menrad et al, 2010), but the underlying mechanisms remain elusive. Raval et al (2005) demonstrated that the effect of HIF-2a on HIF1a protein requires HIF-2a binding to DNA, but concluded that it is indirect and likely involves reduced HIF-1a protein translation.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Specifically, they showed that small interfering RNA (siRNA) for HIF-1a increases HIF-2a protein, whereas overexpression or siRNA for HIF-2a reduces and increases HIF-1a protein, respectively. This dual effect has been reproduced by others using unrelated cell types (Menrad et al, 2010), but the underlying mechanisms remain elusive. Raval et al (2005) demonstrated that the effect of HIF-2a on HIF1a protein requires HIF-2a binding to DNA, but concluded that it is indirect and likely involves reduced HIF-1a protein translation.…”
Section: Introductionmentioning
confidence: 77%
“…This effect is mediated through direct binding of HIF-a subunits to an rHRE in the HIF-1a proximal promoter. There is no reason to think that a similar mechanism does not operate in other cell types exposed to hypoxia or oncogenic signaling (Menrad et al, 2010). Supporting this, activation of HIF-1a/2a signaling in skin fibroblasts and renal proximal tubular epithelial cells by the iron chelator desferrioxamine and the 2-oxoglutarate analog dimethyloxalylglycine reduced HIF-1a mRNA effectively (Supplementary Figure S4).…”
Section: Ravalmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Previous studies have shown that HIF1A contributes to autophagy regulation in hypoxia. 20,[24][25][26][27][68][69][70] The BH3 domains of BNIP3 and BNIP3L, known HIF1A targets, disrupt the BCL2-BECN1 complex, releasing more BECN1 to be involved in the autophagic process. 24 In NP cells, although the BNIP3 level was increased under hypoxia, the absence of a concomitant increase in p-BECN1 Ser93 indicated a possible lack of correlation with autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factors (HIFs), which are heterodimers composed of an α and β subunit, have been implicated in the regulation of the hypoxic response (12,13). HIF-1 was reported to mediate the expression of hundreds of genes, including those for vascular endothelial growth factors, glycolytic enzymes and glucose transporters (14,15).…”
Section: Introductionmentioning
confidence: 99%